Openness, transparency and accountability in public governance: advantages and challenges from the industrial revolution 4.0 - Dang, Minh Tuan (2020)
Today, the use of technology and applications gained from the Industrial Revolution 4.0 is a requirement of good/modern governance to promote disclosure and transparency, thereby contributing effectively in the fight against corruption. However, recent technological advances have also introduced many challenges to governance, especially in the area of accountability in the application of artificial intelligence (AI) in the public sector.